LEARNING LOSS YANG TERJADI PADA PELAKSANAAN PEMBELAJARAN DARING SISWA KELAS IV SEKOLAH DASAR DI GUGUS 2 KECAMATAN BIRINGKANAYA KOTA MAKASSAR - Syamsiah Syamsiah; Amir Pada (PINISI :Journal of Teacher Professional, 2023)
This research is a survey research, which aims to describe the learning loss that occurs in the implementation of online learning for fourth grade elementary school students in Cluster 2, Biringkanaya District, Makassar City. The population of this study were 317 grade IV elementary school students in Cluster 2, Biringkanaya District, Makassar City, while the sample was 177 grade IV elementary school students Cluster 2, Biringkanaya District, Makassar City, which had been selected through a sampling technique with proportionate random sampling. The research data were obtained by distributing questionnaires/questionnaires of learning loss that occurred in the implementation of online learning with 24 written statements. The data analysis technique in this study is descriptive statistical analysis. The results of the learning loss analysis that occur in the implementation of online learning for fourth grade elementary school students in cluster 2 Biringkanaya District, Makassar City in the medium category. The picture of learning loss that occurs in the implementation of online learning for fourth grade elementary school students in cluster 2 Biringkanaya District, Makassar City is that students have difficulty understanding and doing assignments during online learning due to lack of student interest in learning and the explanation of the material provided by the teacher is not clear. So it can be said that the learning process is not optimal.